Composing Professional Human Resource: The Necessity of Excellent Internship Mentoring System - Febriani Putri, Sheila; Maha Putri, Dhika; Purnamasari, Fitri; Puspan- ingtyas, Miranti P; Narullia, Dwi (KnE Social Sciences, 2020)
University is primarily being a wide place or facility to produce capable, intelligent and professional workforce. Students are equipped with various kinds of knowledge theoretically as well as trained through the internship process. However, the findings on graduates who don’t reflect some aspects of professionalism, less competent in each of their fields or even their soft skills should be classified as urgent issues at any rate. Driven by these contrary sides, we highlighted that the less maintained students’ internship period might be a variable for the problems. We started by collecting previous studies on the dissatisfactions from employers about trainees/interns from universities, analyzed the solutions, and triangulated the solutions we proposed by exploring internship masterplan at a university in Indonesia. From all of these steps, we found that appropriate, intensive mentoring ways in the students’ internship period are the main points to create the skills that meet any employers’ demands. We believe that the results of this study will be very useful for those who need answers to the best ways to improve the quality and capabilities of higher education graduates. Keywords: education system, human resource, internship, labor, university graduates